1970
DOI: 10.2464/jilm.20.548
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grain size on Portevin-LeChatelier effect in Al-Mg alloys

Abstract: In order to investigate the effect of grain size on Portevin-Le Chatelier yielding, tensile tests were performed on Al-0.55 and 1 at%Mg alloys having various grain sizes.It was found that the value of ƒÃ0 was decreased and the stress at the onset of P-L effect was increased with the decrease of grain size. The above fact is explained by the effect of grain size on the average velocity of moving dislocations. (Received Aug. 20, 1970) Faculty of Engineering, Doshisha University (Kyoto)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…6(b)). It is reported that the stress amplitude decreases with decreasing amount of the solute Mg element 4) . As for the specimen B, the amount of T phase increases after arti cial aging at higher temperatures (Fig.…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…6(b)). It is reported that the stress amplitude decreases with decreasing amount of the solute Mg element 4) . As for the specimen B, the amount of T phase increases after arti cial aging at higher temperatures (Fig.…”
Section: 4mentioning
confidence: 99%
“…The serrated ow is caused by dynamic strain aging (DSA), where the solute atoms diffuse in the matrix and interact with dislocations in motion during deformation 1,2) . Brief analyses have been done to reveal a great deal about the DSA phenomena with an emphasis on the effects of solute concentration and process factors such as strain, strain rate, deformation temperature and so on [3][4][5][6][7] . As for the microstructural factors, it has been reported that nano-ordered clusters (or G.P.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of the cause of serration generation in Al-Mg alloy using In-situ XRD/DIC simultaneous measurement Hiroki ADACHI 1 *, Tatsuya KITANO 2 , Masahiro HIRATA 2 and Daisuke OKAI 1 Type-B serrations were observed during room-temperature tensile deformation of Al-2.17mass%Mg alloy with an average grain size of 12 μm. Digital image correlation was used to visualize Portevin-Le Chatelier (PLC) bands, and microstructural changes in these bands were observed by in-situ X-ray diffraction measurements using synchrotron radiation at SPring-8.…”
mentioning
confidence: 99%